Effect of ethanol extract of Hedyotis corymbosa (L.) Lamk against parasitemia and hepatomegaly in Plasmodium berghei ANKA-infected mice - Jelita Aprisano Putri; Nabilla Feirizky Chairunnisa; Heny Arwati; Hartono Kahar (Universitas Muhammadiyah Surabaya, 2023)
Malaria is a parasitic infectious disease that remains one of the focuses of world health problems. The ethanol extract of Hedyotis corymbosa has biochemical compounds potentially become a new antimalarial drug. This study aimed to analyze the effect of this extract on parasitemia and hepatomegaly in mice infected with Plasmodium berghei ANKA. Twentyfive BALB/c mice were infected with P. berghei ANKA and grouped into 5 groups. Group 1-3 were treated with 250 mg/Kg BW (HC250), 300 mg/Kg BW (HC300), and 350 mg/Kg BW (HC350) of ethanol extract of H. corymbosa (EEHC), respectively. Group 4 was a positive control (POS) which was given dihydroartemisisnin-piperaquin (DHP) and Group 5 was a negative control (NEG) which was only given CMC Na 1%. Treatments were given orally once a day for four consecutive days. Parasitemia was observed daily on Giemsa-stained tail blood smear. On day 5 the mice were sacrificed, blood were collected by cardiac punctured, the livers were removed and the length, width, and weight were measured. There was no significant difference on parasitemia between Group 1, 2, 3 and NEG. However, the highest inhibition of parasite s growth was found in Group 3 (61.4%. Observation on hepatomegaly, showed that a significant difference on the length of the liver was found between Group 3 and NEG.